Using metacognitive strategies to raise awareness of stress and intonation - Peñuela, Diana Carolina (Colombian Applied Linguistics Journal, 2018)
Few studies have analyzed the impact of language awareness and metacognitive strategies for intelligibility in the context of English as an international language. This qualitative action research study examined the impact of using three metacognitive strategies—overviewing, goal setting, and self-evaluating—to raise adult learners’ awareness of stress and intonation at a private language center in Bogotá. Ten participants enrolled in an advanced English course showed lack of awareness of the use of suprasegmentals (stress or intonation) to communicate intelligibly in a preliminary oral interview. The implementation took three cycles each lasting one hour every day for two weeks. During the first week, the participants were trained to use one metacognitive strategy. During the second week, they identified a suprasegmental feature from video or audio input. Finally, they monitored the use of the feature through the strategy they had learned in the first week. Data were collected via learning logs, recorded artifacts, and field notes. The results showed that students raised awareness in a triadic process that involves metalinguistic, learning, and self-awareness. Results may be useful to revisit the current teaching of pronunciation and to provide insights about the use of elements from the lingua franca core in the Colombian context.